Contamination of Canadian and European bottled waters with antimony from PET containers - Shotyk, William; Krachler, Michael; Chen, Bin (Journal of environmental monitoring, 2006)
Using clean lab methods and protocols developed for measuring Sb in polar snow and ice, we report the abundance of Sb in fifteen brands of bottled water from Canada and forty-eight from Europe. Comparison with the natural abundance of Sb in pristine groundwaters, water bottled commercially in polypropylene, analyses of source waters prior to bottling, and addition of uncontaminated groundwater to PET bottles, provides unambiguous evidence of Sb leaching from the containers. In contrast to the pristine groundwater in Ontario, Canada containing 2.2 ± 1.2 ng l−1 Sb, 12 brands of bottled natural waters from Canada contained 156 ± 86 ng l−1 and 3 brands of deionized water contained 162 ± 30 ng l−1; all of these were bottled in PET containers. Natural water from Ontario bottled in polypropylene contained only 8.2 ± 0.9 ng l−1. Comparison of three German brands of water available in both glass bottles and PET containers showed that waters bottled in PET contained up to 30 times more Sb. To confirm that the elevated Sb concentrations are due to leaching from the PET containers, water was collected in acid-cleaned LDPE bottles from a commercial source in Germany, prior to bottling; this water was found to contain 3.8 ± 0.9 ng l−1 Sb (n = 5), compared with the same brand of water purchased locally in PET bottles containing 359 ± 54 ng l−1 (n = 6). This same brand of water in PET bottles, after an additional three months of storage at room temperature, yielded 626 ± 15 ng l−1 Sb (n = 3). Other German brands of water in PET bottles contained 253-546 ng l−1 Sb (n = 5). The median concentration of Sb in thirty-five brands of water bottled in PET from eleven other European countries was 343 ng l−1 (n = 35). As an independent check of the hypothesis that Sb is leaching from PET, the pristine groundwater from Canada (containing 2.2 ± 1.2 ng l−1 Sb) was collected from the source using PET bottles from Germany: this water contained 50 ± 17 ng l−1 Sb (n = 2) after only 37 days, even though it was stored in the refrigerator, and 566 ng l−1 after six months storage at room temperature.